Differential localization of glutamate receptor subunits at the Drosophila neuromuscular junction. - Marrus, S.B.; Portman, S.L.; Allen, M.J.; Moffat, K.G.; DiAntonio, A. (Journal of Neuroscience, 2004)
The subunit composition of postsynaptic neurotransmitter receptors is a key determinant of synaptic physiology. Two glutamate receptor subunits, Drosophila glutamate receptor IIA (DGluRIIA) and DGluRIIB, are expressed at the Drosophila neuromuscular junction and are redundant for viability, yet differ in their physiological properties. We now identify a third glutamate receptor subunit at the Drosophila neuromuscular junction, DGluRIII, which is essential for viability. DGluRIII is required for the synaptic localization of DGluRIIA and DGluRIIB and for synaptic transmission. Either DGluRIIA or DGluRIIB, but not both, is required for the synaptic localization of DGluRIII. DGluRIIA and DGluRIIB compete with each other for access to DGluRIII and subsequent localization to the synapse. These results are consistent with a model of a multimeric receptor in which DGluRIII is an essential component. At single postsynaptic cells that receive innervation from multiple motoneurons, DGluRIII is abundant at all synapses. However, DGluRIIA and DGluRIIB are differentially localized at the postsynaptic density opposite distinct motoneurons. Hence, innervating motoneurons may regulate the subunit composition of their receptor fields within a shared postsynaptic cell. The capacity of presynaptic inputs to shape the subunit composition of postsynaptic receptors could be an important mechanism for synapse-specific regulation of synaptic function and plasticity.